Polymer immobilized tantalum(v)–amino acid complexes as selective and recyclable heterogeneous catalysts for oxidation of olefins and sulfides with aqueous H2O2. (28th October 2019) - Saikia, Gangutri; Ahmed, Kabirun; Rajkhowa, Chandrasee; Sharma, Mitu; Talukdar, Hiya; Islam, Nashreen S.
Abstract : Polymer supported peroxotantalate based heterogeneous catalysts served as highly efficient, selective and recyclable catalysts for alkene epoxidation and sulfide oxidation with green oxidant aqueous H2 O2 under mild reaction conditions. Abstract : Polymer supported heterogeneous peroxotantalum(v ) catalysts were prepared by anchoring Ta(v )-diperoxo species to chloromethylated poly(styrene–divinylbenzene) resin functionalized with amino acids asparagine (l -Asn) and arginine (l -Arg). The structurally well-defined catalysts, [Ta(O2 )2 (L)2 ] − -MR, [L = asparagine (catalyst 1 ) or arginine (catalyst 2 ) and MR = Merrifield resin], were comprehensively characterized by elemental analysis (CHN, ICP-OES, energy dispersive X-ray spectroscopy), spectral studies (FT-IR, Raman, 13 C NMR, diffuse reflectance UV-vis and XPS), SEM, XRD, Brunauer–Emmett–Teller (BET) and thermogravimetric analysis (TGA). The supported peroxotantalum (pTa) compounds displayed excellent catalytic performance in epoxidation of alkenes with 30% H2 O2, under solvent free reaction conditions. Styrene was epoxidized with >99% selectivity with the highest TOF of 1040 h −1 obtained within 30 min reaction time, whereas the TOF for norbornene epoxidation was 2000 h −1 within 1 h with >95% epoxide selectivity. Furthermore, the immobilized catalysts facilitated chemoselective oxidation of a broad range of organic sulfides to the desired sulfoxides with H2 O2 in methanol, under mild reaction conditions. The oxidations proceeded with a high H2 O2 efficiency percentage and are amenable to ready scalability. The heterogeneous catalysts could be easily recovered and reused for several consecutive catalytic cycles with undiminished activity/selectivity profiles in all cases. The developed catalytic strategies are operationally simple and, being free from halogenated solvent or any other toxic auxiliaries, environmentally clean.